Self-Reported Long-Term Autonomic Function After Laparoscopic Total Mesometrial Resection for Early-Stage Cervical Cancer: A Multicentric Study. Issue 7 (September 2017) - Lucidi, Alessandro; Windemut, Swetlana; Petrillo, Marco; Dessole, Margherita; Sozzi, Giulio; Vercellino, Giuseppe Filiberto; Baessler, Kaven; Vizzielli, Giuseppe; Sehouli, Jalid; Scambia, Giovanni; Chiantera, Vito
Abstract : Objectives: This multicentric retrospective study investigates the early and long-term self-reported urinary, bowel, and sexual dysfunctions in early-stage cervical cancer patients who submitted to laparoscopic total mesometrial resection (L-TMMR), total laparoscopic radical hysterectomy, vaginal-assisted laparoscopic radical hysterectomy, and laparoscopic-assisted radical vaginal hysterectomy. Methods: Cervical cancer patients, FIGO (International Federation of Gynecology and Obstetrics) stage IA2–IB1/IIA1 who submitted to nerve-sparing radical hysterectomy were recruited. Pelvic functions were assessed within 30 days (early outcome) and 12 months after surgery (long-term outcome). Results: Two hundred thirteen subjects receiving nerve-sparing radical hysterectomy were enrolled. Laparoscopic total mesometrial resection was performed in 46 patients (21.6%), total laparoscopic radical hysterectomy in 65 patients (30.5%), vaginal-assisted laparoscopic radical hysterectomy in 54 patients (25.4%), and laparoscopic-assisted radical vaginal hysterectomy in 48 women (22.5%). Operative time was significantly lower in the L-TMMR group (240 minutes; range, 120–670 minutes; P = 0.001). The overall perioperative complication rate was 11.3%, with no statistically significant differences among the 4 groups. Stress incontinence and sensation of bladder incomplete emptying were detected, respectively, in 54 patients (25.6%) and 65 patients (30.7%) with a significantly lower prevalence among those in the L-TMMR group, which resulted, respectively, in 11.1% ( P = 0.022) and 13.3% ( P = 0.036). The prevalence rates of constipation, sensation of incomplete bowel emptying, and effort during evacuation were significantly higher among those in the L-TMMR group, resulting in, respectively, 37% ( P = 0.001), 42.3% ( P = 0.012), and 50% ( P = 0.039). One hundred forty-nine patients (70%) were sexually active. Fifty-eight women (38.9%) reported low enjoyment, 83 women (55.7%) medium enjoyment, and 8 women (5.4%) reported high enjoyment, without statistically significant differences among the 4 groups. Conclusions: Laparoscopic total mesometrial resection is associated with improved long-term urinary autonomic functions and worse gastrointestinal autonomic outcome. Further larger prospective trials are needed to evaluate both the oncological and functional outcomes in order to establish the most appropriate surgical approach for early-stage cervical cancer patients. Abstract : Supplemental digital content is available in the text.